A genome‐wide association study identified new variants associated with mathematical abilities in Chinese children. (22nd February 2023) - Zhang, Liming; Wang, Zhengjun; Zhu, Zijian; Yang, Qing; Cheng, Chen; Zhao, Shunan; Liu, Chunyu; Zhao, Jingjing
Abstract: Mathematical ability is moderately heritable, and it is a complex trait which can be evaluated in several different categories. A few genetic studies have been published on general mathematical ability. However, no genetic study focused on specific mathematical ability categories. In this study, we separately performed genome‐wide association studies on 11 mathematical ability categories in 1146 students from Chinese elementary schools. We identified seven genome‐wide significant single nucleotide polymorphisms (SNPs) with strong linkage disequilibrium among each other (all r 2 > 0.8) associated with mathematical reasoning ability (top SNP: rs34034296, p = 2.01 × 10 −8, nearest gene: CUB and Sushi multiple domains 3, CSMD3). We replicated one SNP (rs133885) from 585 SNPs previously reported to be associated with general mathematical ability associated with division ability in our data ( p = 1.053 × 10 −5 ). In the gene‐ and gene‐set enrichment analysis by MAGMA, we found three significant enrichments of associations with three mathematical ability categories for three genes (LINGO2, OAS1 and HECTD1). We also observed four significant enrichments of associations with four mathematical ability categories for three gene sets. Our results suggest new candidate genetic loci for the genetics of mathematical ability. Abstract : We identified seven genome‐wide significant single nucleotide polymorphisms (SNPs) with strong linkage disequilibrium among each other associated with mathematical reasoning ability (top SNP: rs34034296, p = 2.01 × 10 −8, nearest gene: CUB and Sushi multiple domains 3, CSMD3). We replicated one SNP (rs133885) from 585 SNPs previously reported to be associated with general mathematical ability associated with division ability in our data ( p = 1.053 × 10 −5 ). In the gene‐ and gene‐set enrichment analysis by MAGMA, we found three significant enrichments of associations with three mathematical ability categories for three genes (LINGO2, OAS1 and HECTD1). We also observed four significant enrichments of associations with four mathematical ability categories for three gene sets.